Proliferosphaera, a new genus from India - DEEBA KAMIL and N. PRABHAKARAN, T. PRAMEELA DEVI, NITA MATHUR (Indian Phytopathology, 2012)
Proliferosphaera, anamorph gen. nov. and Proliferosphaera capsici anamorph sp. nov. are proposed to accommodate a eustromatic fungus collected from the fruits of Capsicum annuum L. (Solanaceae) from Gujarat state of India causing die-back and fruit rot disease. The genus is characterized by the presence of dense conidiomata (pycnidia) with distinct zonation and were globose, with one or two ostioles when young, became irregular in shape with successive development of a number of broad and long beaks; attachment of dense mycelium with the matured conidiomata; production of many hyaline, aseptate, thin walled, ellipsoidal to sub-globose conidia with 10 x 2.5-7.5 Î¼m in size having two conspicuous guttules one at each end. Proliferosphaera is recognized as a new genus distinct from the closed genera viz., Capitorostrum, Corniculariella, Cryptosporiopsis, Cytonema, Dinemasporium, Dwiroopa, Endothiella, Monochaetia, Phoma, Phomopsis, Phyllosticta and Seimatosporium in the order Sphaeropsidales both at morphological and molecular (Internal Transcribed Spacer; ITS) analyses. In this article, the type genus Proliferosphaera with type species Proliferosphaera capsici, is described and illustrated.